STRENGTHENING INDONESIA’S MARITIME SOVEREIGNTY: IMPLEMENTING A SINGLE AGENCY MULTI-TASKS MODEL TO COMBAT IUU FISHING - Wartoyo, Franciscus Xaverius; Jaya, Belardo Prasetya Mega; Arafat, Muhammad Rusli; bin Mohd Rusli, Mohd Hazmi; Taufiqurrohman, Asari; Malik, Imam Ibnu; Rakhmatika, Devi (Fakultas Hukum, Universitas Diponegoro, 2025)
Indonesia’s location between the Indian and Pacific Oceans positions it as a crucial maritime route, thereby revealing significant maritime opportunities. This strategic location also presents significant vulnerabilities, especially from foreign vessels involved in unlawful activities, including illegal, unreported, and unregulated (IUU) fishing. IUU fishing represents a widespread issue that threatens regional security and the sustainability of marine ecosystems, ultimately impacting food security and economic viability. This research adopts a normative legal methodology, incorporating an extensive literature review to examine the philosophical underpinnings and regulatory benchmarks pertinent to Indonesia's enforcement framework addressing IUU fishing. This analysis scrutinizes current legal resources and explores the intricate dynamics of overlapping jurisdictions among maritime agencies, intensifying enforcement inefficiencies and generating operational uncertainties. This study proposes implementing the Single Agency Multi-Tasks (SAMT) system as a comprehensive approach to enhance law enforcement efforts targeting foreign vessels involved in IUU fishing within Indonesia's Fisheries Management Areas (FMAs), considering the existing challenges. The SAMT framework aims to centralize authority within the Marine Security Agency (BAKAMLA) to streamline operations and improve regulatory compliance, ultimately contributing to a strong maritime governance structure. The results highlight the importance of implementing legal reforms and establishing coordinated governance mechanisms by national and international maritime regulations. This study significantly enhances the discussion surrounding optimizing fisheries management and reinforcing Indonesia’s sovereignty in its maritime areas while also tackling the widespread challenges IUU fishing activities present.